In vivo versus in vitro assays for assessment of T- and B- cell function. - Bachmann, M; Kündig, T (1994)
As mice deficient in a particular gene provide an increasing number of novel in vivo models, in vivo assays that examine immune function are becoming a central issue. We found that the sensitivities of in vivo and in vitro assays are strikingly different. These differences have important implications for the interpretation and biological relevance of results.